Vegetarianism as religious observance: Comparative Study of Maitreya Buddhists and Adventist Christians - Tia Amalia Nurjanah; Ilim Abdul Halim; Rika Dilawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2023)
Religion is a human guide in living life. Religion regulates all aspects of life so that humans will always be good people to God and to fellow human beings. They are included in the selection of food consumed daily both in Buddhist Maitreya and Adventist Christianity. Each religion has regulations on how to choose food and become a vegetarian for each adherent. This study aims to discover the vegetarian tradition in Maitreya Buddhism and Adventist Christianity, along with the agreements and differences between the two religions. The research model used is qualitative research. While the method used is a comparative method. The comparative method is a method used to compare two data sources to find agreement and differences. The formulation of the thoughts in this study is the theory put forward by Joachim Wach regarding three religious expressions (theoretical, practical, and sociological). Based on research and discussion, it is known that the vegetarian tradition in Buddhist Maitreya and Adventist Christianity has agreements and differences. The similarity lies in how Maitreya Buddhism and Adventist Christianity both have theoretical doctrines about what they will get in the afterlife if they become vegetarians so that their adherence to religion can be seen from their lifestyle as vegetarians. While the difference lies in the selection of food, they consume daily. Maitreya Buddhists tend to avoid all forms of meat, while Adventist Christians still eat fish and tolerate meat when they are sick.